Phytochemical Contents and Antioxidant Activity of Dysoxylum densiflorum Extract and Fractions - Sundowo Andini; Antika Lucia Dwi; Meilawati Lia; Randy Ahmad; Artanti Nina; Hanafi Muhammad (E3S Web of Conferences, 2024)
Many studies have been carried out on the use of natural product compounds as an alternative medicine. Dysoxylum densiflorum is a plant that is commonly found in tropical countries and is used as an alternative treatment in local communities for several diseases. Our current study aims to determine the content of phytochemicals, total phenol, and total flavonoids from D. densiflorum leaves and stem bark methanol extract. The extraction was performed by the maceration method using methanol solvent and then fractionated into hexane, ethyl acetate, and methanol. A phytochemical screening was performed to determine the content of alkaloids, flavonoids, terpenoids, tannins, and saponins. The total phenol contents of the extract were determined by Folin-Ciocalteu using gallic acid as a standard. Total flavonoid were determined by alumunium chloride colorimetric methods, with quercetin as the standard. The antioxidant activity was determined by using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging and 2,2’-azino-bis-(3 ethylbenzothiazoline)-6-sulfonic Acid (ABTS) assay. The results of phytochemical screening showed that the extract and fractions of D. densiflorum leaves contained flavonoids, terpenoids, tannins, and saponins. The methanol extract and fractions of D. densiflorum stem bark contained flavonoids, tannins, and saponins. The total phenol analysis showed that leaves and stem bark methanol fractions had the highest content, at 4.631 mg GAE/g and 3.011 mg GAE/g, respectively. While the total flavonoids analysis showed that leaves methanol extract and bark ethyl acetate fraction had the highest content compared to other samples from the same origin, which are 49.585 mg QE/g and 63.432 mg QE/g, respectively. Antioxidant test results using DPPH radical scavenging and the ABTS assay obtained the highest IC50 values, respectively, in the stem bark methanol fraction of 104.092 μg/mL and the leaves ethyl acetate fraction of 8.49 μg/mL. The ethyl acetate fraction of D. densiflorum leaves contains the highest antioxidant activity. The results indicate that D. densiflorum extracts and fractions have antioxidant potential. Further research is required to identify compounds that act as antioxidants.